The Third Wave of Technology in Education - Juan Pedro Rodriguez (GoAcademica Research & Publishing, 2022)
Some of the criteria that are set out below may guide you to a reflection about how should be define the next curriculums and profiles of the teachers in the context of the development of these technologies. The interest that animates this essay deals with a conceptual appreciation of how we imagine and understand the bond and the structure of the relationship that occur between new technologies and education. This interest deals with a conceptual appreciation of how we imagine and understand the bond and the structure of the relationship that occur between new technologies and education. Within the context of the changing social composition of the relationship between education and human growth and quality of life, there is an obvious requirement for the school to become more in tune with contemporary tendencies in information technology and communication.